Vocational School Revitalization: Opportunities and Challenges (Case Study of Implementation of West Nusa Tenggara Governor Policy Number 75 of 2020) - Iqbal, Muhammad Atha'; Kamariani, Baiq Dewi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The aim of this research is to understand the opportunities and challenges of implementing the vocational school revitalization policy at SMKN 01 Jerowaru, East Lombok. This research is a qualitative descriptive study with the research location at SMKN 01 Jerowaru, East Lombok. Collection techniques through interviews. Data analysis in this research uses the Interactive Model data analysis from Miles, Huberman and Saldana (2014). The results of this research show that there are opportunities and challenges for SMKN 01 Jerowaru in implementing the Vocational School Revitalization policy. Where opportunities and challenges come internally and externally. where the research results in this year, the opportunity for policy implementation obtained by SMK 01 Jerowaru is the collaboration between the school and industry in the form of an agreement in creating a curriculum, as a follow-up to this in the form of activities to increase competency and develop skills for teachers through the OJT program. Meanwhile, the challenge is the provision of practical equipment such as bratending and barista practice rooms which still do not exist. For the culinary arts department, even though they already have an RPS equipped with IDUKA standard equipment, the production of products in schools is still not productive and unable to produce a surplus.